Long-Term Dynamics of a Well-Characterised Food Web: Four Decades of Acidification and Recovery in the Broadstone Stream Model System - Layer, Katrin; Hildrew, Alan G; Jenkins, Gareth B; Riede, Jens O; Rossiter, Stephen J; Townsend, Colin R; Woodward, Guy (Advances in ecological research, 2011)
An understanding of the consequences of long-term environmental change for higher levels of biological organisation is essential for both theoretical and applied ecology. Here, we present four decades of data from the well-characterised Broadstone Stream community, detailing biological responses to amelioration of acidification and the recent invasion of a top predator (brown trout, Salmo trutta L.) that was previously excluded by low pH. After several decades of reductions in acidifying emissions, species characteristic of less acid conditions have started to invade or recolonise Broadstone and other European freshwaters, but these signs of biological recovery are still patchy and have lagged behind chemical recovery. One possible explanation for slow recovery is ecological inertia arising from the internal dynamics of the food web, a hypothesis we investigate here using a combination of surveys, experiments and mathematical modelling. The invasion of this hitherto invertebrate-dominated system by a large, generalist vertebrate predator could be expected to alter the structure and stability of the food web. Long-term survey data revealed that the community has experienced waves of invasions or irruptions of progressively larger predators since the 1970s, as pH has risen. Intra-annual fluctuations in prey populations have become increasingly damped and the mean abundance of many species has declined, although none of the previously common taxa have been lost. This suggests that predation, rather than simple chemical tolerance, plays a key role in determining the trajectory of recovery, as the top-down effects of the generalist predators spread diffusely through the reticulate food web. Dynamical simulations indicate that the food web may have become less robust over time as pH has risen and larger predators have become dominant. These results suggest that, though none of the original suite of large invertebrate predators has been driven to local extinction, such an eventual outcome is feasible.